London [videorecording (DVD)] : Babylon - Temple, Julien; Temple, Julien; Temple, Julien (Docurama, 2013)
From musicians, writers and artists to dangerous thinkers, political radicals and, above all, ordinary people, this is the story of London's immigrants, its bohemians and how together they changed the city forever. Features archival footage.